Understanding expertise-based training effects on the software evaluation process of Mathematics Education teachers - Incikabi, Lutfi; Sancar Tokmak, Hatice (Informa UK Limited, 2012)
This case study examined the educational software evaluation processes of pre-service teachers who attended either expertise-based training (XBT) or traditional training in conjunction with a Software-Evaluation checklist. Forty-three mathematics teacher candidates and three experts participated in the study. All participants evaluated educational software selected by the novice groups in accordance with Software Evaluation checklist. Two analysis procedures were applied: (a) similarities in rankings of the same educational software between the XBT and traditional groups using the checklist and (b) organizing common themes in the data collected through journals and in-class observations. The results showed that the expert-XBT group agreement rate was 63%, while the expert-traditional group agreement rate was 42%. Moreover, the XBT group showed a similar approach to the experts, including assessing each criterion and evaluating the software as a whole.
Keywords: 4. Education; 16. Peace & justice